The Effectiveness Of Tekun Project Towards The Entrepreneurs In Kota Samarahan, Sarawak/Fadzrina Anizan Misli, Nor Fazreen&Mohamad Eddie - Misli, Fadzrina Anizan; Mohamad Eddie, Nor Fazreen (2015)
Alhamdulillah. All praises to Allah SWT for the strength and His blessings in completing this research. This was a challenging project for us. But, this is a wonderful experiences we ever had. Thank you so much to peoples that helps us for completing thisresearch. First is for our supervisor, Mr. Lt. Col. Saiful Anwar Md. Ali (R) for his guidance and advices. He keep motivates us in our research eventhough there is more challenges in our research. We would like to express our deepest thanks Madam Noorfadhleen Mahmud for her guidance to us start our research. Without her advice and guidance, we are sure that we gonna faced so many troubles because both of us has no experience conducting research before. Thanks a lot to Dr. Kuldip Singh also for helping us in the findings part. Helps us on SPSS session. Special thanks to our parents. They has gives their support to us both in emotional and financial support. They always gives us motivaton and encouragement eventhough they are far from us. Also to our friends. They gives us support and continuous encouragement to finish this research. They helps us to finds the respondents eventhough the respondents are not in the same place, but they keep accompanied us to meet the respondent. Thanks a lot to them. We hope that our topics could gives the ideas to other researcher to conducting this topic again. This is not often topic conducted by the researcher and still many peoples have no ideas about TEKUN and its roles. So, we hope we gives some great output to other researcher and to those who read about our research.